Peran Guru dan Orang Tua dalam Mengembangkan Kemandirian Anak Usia 5-6 Tahun di Kelurahan Talang Benih Kecamatan Curup - Gayatri, Niken; Akbari (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2025)
Early childhood independence is a fundamental aspect shaped through the interaction between home and school environments. However, previous studies have focused more on urban contexts and emphasized the role of one party, either parents or teachers, without examining their synergy in a rural community setting. This study aims to describe the roles of parents and teachers in developing the independence of children aged 5-6 years in Talang Benih Village, Curup District, a rural area with distinct socio-cultural characteristics. A descriptive qualitative approach was applied, with data collection techniques including participatory observation, semi-structured interviews, and documentation. The research subjects involved parents, teachers, and children aged 5-6 years selected purposively. The results reveal that children's independence develops through three main roles performed synergistically by parents and teachers: as guides, motivators, and facilitators. Parents tend to use emotional and contextual approaches at home, while teachers emphasize structure, procedure, and social reinforcement at school. This synergy creates a consistent and supportive environment for children to internalize the values of independence. The study concludes that close collaboration between parents and teachers, albeit with different approaches, is key to effectively fostering early childhood independence in a rural environment. These findings provide an important contribution to the development of contextual and culturally-based early childhood education models.